Perencanaan Sistem Jaringan Distribusi Air Bersih Kecamatan Panggul Kabupaten Trenggalek Provinsi Jawa Timur - Rafli, Muhammad Farhan Nur; Suhardono, Agus; Harifa, Ayisya Cindy (Journal of Civil Engineering, 2025)
Panggul District is a highland area that has 17 villages in 1 District Capital where 4 villages are served by PDAM and 13 villages are still not served. So the aim of writing this thesis is to calculate the population in 2038, calculate water needs, create a pipe network design distribution and reservoir dimensions, knowing the methods for implementing network planning and also calculating the cost budget for implementing distribution network work so that the community can meet their water needs at all times. The data required is population data, spring discharge data, topographic map data and also land use and road network maps, and also work unit price analysis data. To get appropriate results, the data will be processed manually using Microsoft Excel and AutoCad applications. The calculation results show that the population in 2038 will be 84,302 people, using two springs, namely Sumber Joso with a discharge of 51.26 lt/sec and Sumber Pucung of 50.3 lt/sec, the discharge for clean water needs is 73,863 lt/sec. , the pipes used in planning the clean water distribution pipe network are HDPE PN 16 pipes with details of 6 inch diameter pipe 177.60 m long, 5 inch diameter pipe 40270.10 m long, 4 inch diameter pipe 11914.50 m long, 3 diameter pipe inch along 22915.90 m, 2 2/1 inch diameter pipe along 2819.80 m, 1 ½ inch diameter pipe along 23922.5 m, and ¾ inch diameter pipe along 9995.40 m. With the dimensions of the first reservoir being 80 m3, then the dimensions of the second reservoir are 56 m3. Using a pump with dimensions of 100 x 80 m and 50 x 40 m, to complete this work a Budget Plan (RAB) of Rp. 34.012.958.000,00 (Thirty-Four Billion Twelve Million Nine Hundred Fifty-Eight Thousand Rupiah).